Quality of Reduction Influences Outcome After Locked-Plate Fixation of Proximal Humeral Type-C Fractures. (2nd November 2016) - Schnetzke, Marc; Bockmeyer, Julia; Porschke, Felix; Studier-Fischer, Stefan; Grützner, Paul-Alfred; Guehring, Thorsten
Abstract : Background: The aim of this study was to determine if fracture reduction, fracture pattern, and patient-related factors influence clinical outcome after locked-plate fixation of displaced proximal humeral fractures. Methods: Ninety-eight patients (mean age, 61.1 ± 11.2 years) with a proximal humeral fracture involving the anatomical neck (type C according to the OTA/AO classification system) were included. Clinical outcome was determined by age and sex-adjusted Constant score (CS%) and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Fracture reduction was quantitatively determined by 3 parameters (head-shaft displacement, head-shaft alignment, and cranialization of the greater tuberosity), and patients were divided into groups according to anatomical reduction, acceptable reduction, or malreduction. Relative risk (RR) for complications, revision surgery, and inferior clinical outcome (CS of <50%) was determined according to the quality of fracture reduction and fracture pattern (disruption of the medial hinge; type-C3 fracture) and patient-related factors (age; comorbidities). Results: After a mean of 3.1 ± 1.5 years, the mean CS% and DASH score were 54.8% ± 28.0% and 31.9 ± 24.8, respectively. The complication rate was 32.7% (n = 32), and 27 patients (27.6%) required revision surgery. Anatomical or acceptable fracture reduction was achieved in 40 (40.8%) of the patients. This resulted in a significantly lower complication rate (20.0% compared with 41.4% among the patients with malreduction; p = 0.027), a trend of lower revision rate (20% compared with 32.8%; p = 0.165), and better clinical outcome (mean CS% of 65.4% ± 28.2% compared with 47.6% ± 25.7%; p = 0.002) without a higher risk for osteonecrosis of the humeral head (5% compared with 10.3%). Cranialization of the greater tuberosity of >5 mm (n = 25), head-shaft displacement of >5 mm (n = 50), and valgus head-shaft alignment (n = 12) all increased the RR for inferior clinical outcome by twofold to threefold. Conversely, a patient age of >65 years (n = 31) and an OTA/AO type-C3 fracture pattern (n = 38) were not significantly associated with complications and inferior clinical outcome (RR, 0.9 to 1.8). Conclusions: Anatomical fracture reduction with a locked plate significantly improved the clinical outcome of unstable and displaced proximal humeral fractures involving the anatomical neck. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.